2003
DOI: 10.1017/s0033291703007761
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and diagnosis of social phobia in the clinic and the community

Abstract: I have been asked to comment on the three articles on social phobia in this issue of Psychological Medicine. The three papers in one way or another concern themselves with important issues in the assessment and diagnosis of social phobia (also known as social anxiety disorder; Liebowitz et al. 2000). I do so with the caveat that I am an author on one of the papers and do not claim the same degree of objectivity in examining my own work as I do in examining the work of others. The three papers concern the psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The exact characteristic of the relationship between avoidance and anxiety has received limited attention (Heimberg, 2003). One reason for this might be that in clinical populations anxiety and avoidance are often difficult to distinguish, because at a clinical level avoidance and anxiety will most often be highly correlated.…”
Section: Social Phobia and Social Fearsmentioning
confidence: 99%
“…The exact characteristic of the relationship between avoidance and anxiety has received limited attention (Heimberg, 2003). One reason for this might be that in clinical populations anxiety and avoidance are often difficult to distinguish, because at a clinical level avoidance and anxiety will most often be highly correlated.…”
Section: Social Phobia and Social Fearsmentioning
confidence: 99%
“…Data obtained by the National Comorbidity Survey indicate that the adult lifetime prevalence of SAD is 13.3% [2]. Recent research also indicated that the 12-month prevalence rate of SAD was 2.48%~7.9% and that the lifetime prevalence was about 3.8%~14.4% [3, 4]. The highly comorbid nature of SAD, which often occurs along with depression, panic disorder, and alcohol abuse, is well established [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Before undertaking this investigation, we considered evidence from previous studies of a strong positive correlation between measures of social anxiety and measures specifically developed to tap avoidance of social-evaluative situations (e.g., r ¼ .91; Heimberg et al, 1999). As proposed by Heimberg (2003) and Heimberg et al (1999), the strength of such relationships raises the possibility that these measures may not in fact be tapping different constructs. To avoid this problem in measurement, our study aimed to use a measure of avoidance that was specifically developed to tap the construct of avoidance, independent of disorder-specific concerns and symptoms (i.e., an instrument that is transdiagnostic).…”
Section: Introductionmentioning
confidence: 99%